2013
DOI: 10.1080/09540105.2012.689816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antibiotic therapy on the gastrointestinal microbiota and the influence ofLactobacillus casei

Abstract: Aims of methods. Effects of intervention with Lactobacillus casei Shirota (LcS) on the incidence of antibiotic-associated diarrhoea (AAD), Clostridium difficile infection (CDI) and changes in faecal microbiota were analysed using C. difficile ELISA (678 patients), qPCR using 16S rRNA group-specific primers, C. difficile-toxin kit and polymerase chain reaction/denaturing gradient gel electrophoresis (56 patients). Results. As much as 18.5% of antibiotic treated group developed AAD, but only 5% of patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
0
24
0
1
Order By: Relevance
“…There is evidence that colonic probiotic bacteria, including LAB such as Lactobacillus acidophilus, and Bifidobacteria (De Petrino, De Jorrat, De Budeguer, & Perdigón, 1997;Pirker et al, 2013), may positively modulate certain colon microbial enzymes that play a role in diet-related diseases (Oršolić, 2009). For example, β-glucuronidase is an inducible enzyme elaborated by anaerobic E. coli, Peptostreptococcus, Bacteroides and Clostridia.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that colonic probiotic bacteria, including LAB such as Lactobacillus acidophilus, and Bifidobacteria (De Petrino, De Jorrat, De Budeguer, & Perdigón, 1997;Pirker et al, 2013), may positively modulate certain colon microbial enzymes that play a role in diet-related diseases (Oršolić, 2009). For example, β-glucuronidase is an inducible enzyme elaborated by anaerobic E. coli, Peptostreptococcus, Bacteroides and Clostridia.…”
Section: Introductionmentioning
confidence: 99%
“…From clinical point of view, probiotic supplementation resulted in reduced diarrhea-like bowel movements (Koning et al, 2008), and reduced AAD incidence (Pirker et al, 2013). In the other studies (Engelbrektson et al, 2009;Plummer et al, 2005), no clinical outcomes were reported.…”
Section: Resistance Genementioning
confidence: 93%
“…In a randomized controlled trial, 40 healthy subjects were administered a probiotic combination (Bifidobacterium lactis Bl-04, B. lactis Bi-07, Lactobacillus acidophilus NCFM, Lactobacillus paracasei Lpc-37 and Bifidobacterium bifidum Bb-02) or placebo during and after a 7-day challenge with a combination of amoxicillin and clavulanate. Similarly, in a probiotic intervention study, a 5-day antibiotic treatment reduced the diversity and abundance of fecal bacterial groups in 56 patients, as measured by quantitative polymerase chain reaction and denaturing gradient gel electrophoresis (Pirker et al, 2013). The similarity of bacterial community to baseline was decreased significantly during antibiotic treatment.…”
Section: Resistance Genementioning
confidence: 97%
See 1 more Smart Citation
“…The means and their variances were calculated for copies in PCR replicas according to [20]. We used tenfold serial DNA dilutions of L. Shirota as well as a mix of strains previously used and described by Pirker et al [26] to construct standard curves for evaluating PCR reaction efficiency. Further, the copy numbers of these standards were used to calculate DNA copies/µl per sample.…”
Section: Methodsmentioning
confidence: 99%